2007
DOI: 10.1002/crat.200610784
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of gel grown calcium pyrophosphate tetrahydrate crystals

Abstract: Formation of calcium pyrophosphate dihydrate (CPPD) crystals in soft tissues such as cartilage, meniscus and synovial tissues lead afflictions. The appearance of these crystals in the synovial fluid give rise to acute arthritis attack, which is known as pseudo-gout. The growth of calcium pyrophosphate crystals in gel medium can mimic the growth in a body. In the present study, calcium pyrophosphate tetrahydrate (CPPT) crystals are grown by a single diffusion gel growth technique and characterized by powder XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…As the frequency increases, a point will be reached where the space charge cannot sustain and comply with the variation of external field and hence the polarization decreases, which gives rise to diminishing values of dielectric constant. However, the nature of variation of dielectric constant with frequency of applied field suggests comparatively very less changes in the low frequency region unlike in calcium pyrophosphate tetrahydrate crystals [27]. The dielectric constant values of Fe−Mn−Co levo-tartrate crystals are comparatively less responsive to the variation of frequency of applied field in the range studied.…”
Section: 4h 2 Omentioning
confidence: 76%
“…As the frequency increases, a point will be reached where the space charge cannot sustain and comply with the variation of external field and hence the polarization decreases, which gives rise to diminishing values of dielectric constant. However, the nature of variation of dielectric constant with frequency of applied field suggests comparatively very less changes in the low frequency region unlike in calcium pyrophosphate tetrahydrate crystals [27]. The dielectric constant values of Fe−Mn−Co levo-tartrate crystals are comparatively less responsive to the variation of frequency of applied field in the range studied.…”
Section: 4h 2 Omentioning
confidence: 76%
“…The authors have applied the Coats and Redfern relation (Coats and Redfern 1964) to evaluate the kinetic parameters for dehydration process from the thermogram. The Coats and Redfern relation is as follows, which has been discussed in detail elsewhere (Parekh and Joshi 2007) …”
Section: Resultsmentioning
confidence: 99%
“…The values of activation energy and frequency factors were calculated from the plot, which are given in table 2. Thermodynamic parameters were also calculated using standard formulae reported elsewhere (Parekh and Joshi 2007). Table 2 shows the values of these parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resonance observed at 723 cm -1 is attributed to symmetric P-O-P bridge vibration, while the resonance centered at *550 cm -1 can be attributed to O-P-O bonding. The absorptions between 400 and 520 cm -1 are due to the presences of oxygen-calcium bonds [20]. Taken together, the FTIR spectrum showed that the product formed in 1.0 M K 2 HPO 4 solution at pH = 7.0 contained the (P 2 O 7 ) 2-, (HP 2 O 7 ) 3-, and (PO 4 ) 3-groups, indicating the presence of a pyrophosphate, as well as a phosphate material.…”
Section: Composition and Phase Analysis Of Reacted 45s5c Microspheresmentioning
confidence: 99%